KEDAULATAN POPULER DI TENGAH KEDAULATAN NEGARA, YURIDIKSI DOMESTIK, DAN INTERVENSI - Zein, Patra M (Global: Jurnal Politik Internasional, 2004)
Under the theme of state's sovereignty, this article puts intervention as its main framework, from the use of traditional threats, i.e. the threat of physical power and state's illegal actions, to the indirect threats which are contained by international trade's unfair conduct. Using international law perspective as its background, this article describes the "death" of absolute sovereignty as a concept. Nowadays, the concepts of sovereignty are dominated by interventions and the new growing concept of popular sovereignty. In line the doctrine of domestic jurisdiction must also face a real challenge from the borderless universal jurisdiction. The last point with this tendency, of this article is marked by a statement that questions Indonesia's sovereignty as a state.